2018
DOI: 10.1111/mmi.14125
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis of ToxR is controlled by cysteine‐thiol redox state and bile salts in Vibrio cholerae

Abstract: Abbreviated Summary: Virulence gene regulation in Vibrio cholerae is highly complex, comprising several transcriptional activators and decision check points. The ToxRS complex is a key regulator that is subjected to regulated intramembrane proteolysis (RIP). The participating interaction partners were characterized, addressing DegS, DegP, ToxS and factors influencing ToxR-RIP, such as bile acids and the cysteine redox state of ToxR. In Vibrio cholerae, virulence gene expression is regulated by a transmembrane-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 63 publications
6
52
0
Order By: Relevance
“…This, based on structural homology with VtrAC, stabilizes the binding interface between ToxR and ToxS. Such an increase in stability is consistent with observations regarding the double cysteine mutant degradation in Lembke et al (Lembke et al, 2018). Interestingly it has been observed that ToxS enhances ToxR intra-chain disulfide bond formation (Ottemann and Mekalanos, 1996).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This, based on structural homology with VtrAC, stabilizes the binding interface between ToxR and ToxS. Such an increase in stability is consistent with observations regarding the double cysteine mutant degradation in Lembke et al (Lembke et al, 2018). Interestingly it has been observed that ToxS enhances ToxR intra-chain disulfide bond formation (Ottemann and Mekalanos, 1996).…”
Section: Discussionsupporting
confidence: 88%
“…ToxS, an integral membrane protein with a periplasmic domain, augments ToxR activity (Miller et al, 1989) and protects ToxR from degradation in conditions of stationary growth and alkaline pH (Almagro-Moreno et al, 2015;Lembke et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the cysteine residues in ToxR are associated with its transcriptional activity through intramolecular disulfide bond formation. Moreover, they also provide a signal for proteolysis once they appear in their reduced form (Ottemann and Mekalanos, 1996;Fengler et al, 2012;Lembke et al, 2018).…”
mentioning
confidence: 99%
“…Red circles in ompU and ompT indicate the ToxR binding sites and the transcriptional start sites are marked with arrows for each promoter. (Mey et al, 2015;Lembke et al, 2018). ToxR activation by bile salts depends on the function of ToxS.…”
Section: Control Of Virulence By the Toxr Regulonmentioning
confidence: 99%